"What is my purpose?" Artificial Sentience Having an Existential Crisis in Rick and Morty - Alexander Maxwell (Alfredo Mac Laughlin, 2021)
The American television show Rick and Morty, an animated science fiction sitcom, critiques speciesism in the context of bleak existentialist philosophy. Though the show focuses primarily on human characters, it also depicts various forms of artificial sentience, such as robots or clones, undergoing existential crises. It explicitly effaces any distinction between human sentience and artificial sentience, forcefully treating all sentient life with an equivalent respect (or disrespect). The show also problematizes human speciesism in relationship to terrestrial and extra-terrestrial life.